...keeps the doctor away - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
A group of researchers from the Ethiopian Health and Nutrition Research Institute and Wageningen University in the Netherlands, looked into the low rate of growth of healthy infants in rural Ethiopia and concluded after extensive nutrition trials...